I Feel a Foot! - Maranke Rinck (United States Lemniscaat USA, 2008)
"Between two trees, high above grass and ground, Turtle, Bat, Octopus, Bird and Buck are sleeping in a hammock. Suddenly, Turtle opens his eyes. 'Hey, ' he whispers. 'Do you hear what I hear?'" Each animal's imagination runs wild with what wild creature may be making the sound they all hear. Is it a giant turtle? Or a bird with a giant beak? Perhaps it is Bat-Tur-Octo-Bird- Buck. Luckily for the small animals, it isn't any of these creatures. It is just their old friend Elephant who was out wandering around. The animals invite him to join them in the hammock and soon the wild imaginings about the night noises begin all over again.
Keywords: Circle Time Book - Awe / Wonder -- Circle Time Book - Awe / Wonder